Forensic computer science as way of test in Ecuador - Pino Icaza, Edith (Revista Universidad de Guayaquil, 2010)
The onus probandi (burden of proof), is an aphorism that expresses in a legal process that he who asserts something must prove the statement. In the procedural law of evidence, comes to see, is the probability of the existence of a thing, is any material or significant mark, which is perceived through the senses and has connection with the act intentional. The company together with the crime phenomenon is an area subject to constant fluctuations, technological innovations that help refine difficult to prosecute illegal acts, since the very precariousness of the criminal legal system reinforces the tendency not to report these crimes to avoid alarm or disrepute by his knowledge that could arise, so it is necessary to identify the loopholes in the implementation of mechanisms in relation to research new computer fraud and determine to where legal proceedings are moving our evidence. Hence the fact of maturing the idea of imple[1]menting computer forensics in Ecuador and investigative mechanism that can be incorporated to process digital evidence.
Keywords: Computer; Forensia; Phishing; Internet; Hacker; Software; Hardware; Browsing; fraud; piracy